Necessity and challenges for the post-pandemic Hangzhou Asian Games: An interdisciplinary data science assessment - Guo, Jianwei; Zhang, Xiangning; Cui, Dandan (Frontiers in Psychology, 2022)
Background: The postponement of the Hangzhou Asian Games has reignited controversy over whether it is necessary and safe to hold. This study aimed to assess its necessity for Asian elite sport and the challenges brought by the COVID-19 pandemic through a joint data science research on elite sport and public health Internet big data. Methods: For necessity, we used 7 pre-pandemic Asian Games to investigate its long-term internal balance, and 6 pre-pandemic Olympic Games to examine its contribution to the external competitiveness of Asian sport powers through bivariate Pearson correlation analyses between sport variables and holding year. For challenges, we used Johns Hopkins COVID-19 data and Tokyo 2020 Olympic data to quantify the past impact of the pandemic on elite sport by another correlation analysis between pandemic variables and the change in the weighted score of medal share (CWSMS), built a transferable linear regression model, transferred the model to Jakarta 2018 Asian Games data, and eventually forecasted the possible impact of the pandemic on the results of the Hangzhou Asian Games. Results: The proportion of gold medal countries in the Asian Games showed a long-term upward trend (Pearson r (7) =0.849, p<0.05), and the share of medals won by Asian countries showed a significant increasing process (Pearson r (6) =0.901, p<0.05). The cumulative number of COVID-19 deaths was most significantly correlated to CWSMS (Pearson r (100) =-0.455, p<0.001). The total Olympic model output of Asian countries was 0.0115 in Tokyo 2020 and is predicted to be 0.0093 now. The prediction for CWSMS in Hangzhou was 0.0013 for China, 0.0006 for Japan, and 0.0008 for South Korea. Conclusion: We documented that Asian Games played a significant role in the long-term balanced internal structure and the increasing global competitiveness of Asian elite sport. We proved that the COVID-19 pandemic has significantly affected Olympic performance of countries worldwide, while the competitive performance in Hangzhou Games would be less affected than the world average level. This study also highlights the importance of interdisciplinary data science research on large-scale sport events and public health.